THE EFFECT OF TAXES, FOREIGN OWNERSHIP, AND DEBT COVENANT ON TRANSFER PRICING WITH FIRM SIZE AS MODERATION - Anjani, Sela; Handarini, Dwi; Mardi, Mardi (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The purpose of this research is to verify and investigate the moderating effect of firm size on the effects of taxes, foreign ownership, and debt covenants on transfer pricing. Financial reports and annual reports of companies that were listed on the Indonesia Stock Exchange (IDX) for 2020-2021 are used as secondary data sources in this research with a quantitative approach. Based on the purposive sampling technique, 71 companies were obtained that met the criteria, bringing the total sample to 142 data. Multiple regression analysis uses the Ordinary Least Square (OLS) approach with the help of the EViews 12 application. The research's findings demonstrate that foreign ownership and debt covenants have an effect on transfer pricing, but taxes have no effect on transfer pricing. Then firm size cannot moderate taxes and debt covenants on transfer pricing, but can moderate the influence of foreign ownership on transfer pricing. Simultaneously, tax, foreign ownership, debt covenants, firm size as a moderating variable, and interaction variables influence transfer pricing with the coefficient of determination in this study only being 17.55%, which means there are still 82.45% of other variables that can influence transfer pricing.